Experimental evidence of warming-induced flowering in the Mediterranean seagrass Posidonia oceanica. (September 2018) - Ruiz, J.M.; Marín-Guirao, L.; García-Muñoz, R.; Ramos-Segura, A.; Bernardeau-Esteller, J.; Pérez, M.; Sanmartí, N.; Ontoria, Y.; Romero, J.; Arthur, R.; Alcoverro, T.; Procaccini, G.
Abstract: Sexual reproduction in predominantly clonal marine plants increases recombination favoring adaptation and enhancing species resilience to environmental change. Recent studies of the seagrass Posidonia oceanica suggest that flowering intensity and frequency are correlated with warming events associated with global climate change, but these studies have been observational without direct experimental support. We used controlled experiments to test if warming can effectively trigger flowering in P. oceanica . A six-week heat wave was simulated under laboratory mesocosm conditions. Heating negatively impacted leaf growth rates, but by the end of the experiment most of the heated plants flowered, while controls plants did not. Heated and control plants were not genetically distinct and flowering intensity was significantly correlated with allelic richness and heterozygosity. This is an unprecedented finding, showing that the response of seagrasses to warming will be more plastic, more complex and potentially more resilient than previously imagined. Highlights: A simulated heat wave induced flowering in Posidonia oceanica . Flowering intensity was significantly correlated with allelic richness and heterozygosity. Heat induction of flowering could be considered an adaptive strategy of the species toward global changes. The species response is potentially more resilient than previously imagined.